Narrative Study of Teaching Strategies and Challenges Encountered by Teachers in Synchronous Online Classes - Kristine Anne Dimaculangan; Hanifa Hadji Abas; Celestie S. Quinto (International Journal of Social Learning (IJSL), 2022)
The COVID-19 pandemic urged a dramatic shift in the educational landscape, whereby digital platforms are utilized in teaching and learning. This new setup has posed challenges in teaching mathematics; hence, this study was conceptualized to explore the different teaching strategies and challenges math teachers encountered in their synchronous online classes (SOC). It aimed to draw analysis and increased understanding of the experiences related to teaching strategies and challenges, focusing on two essential aspects of teaching and learning: content and student engagement. Online in-depth interviews involving nine (9) Junior High School mathematics teachers of a private academic institution in Southern Luzon were conducted for data gathering. Results depict two significant themes as the participants' strategies in their SOC: teacher-directed instruction and motivational strategies.Meanwhile, three major themes emerged as challenges encountered by the participants: the role of the teacher, time constraints, and students' responsiveness. Findings suggest that some of the difficulties in synchronous online teaching may have resulted from the tendency to replicate face-to-face teaching in a virtual classroom and lack of technological proficiency. Hence, opportunities to enhance teachers’ knowledge and skills in digital pedagogies and more student-centered online teaching approaches can be a gateway to address the challenges posed.